Effect of thermocycling on roughness of nanofill, microfill and microhybrid composites - Santos, Paulo Henrique dos [UNESP]; Catelan, Anderson; Guedes, Ana Paula Albuquerque [UNESP]; Suzuki, Thais Yumi Umeda [UNESP]; Godas, Andre Gustavo de Lima [UNESP]; Briso, André Luiz Fraga [UNESP]; Bedran-Russo, Ana Karina (Informa Healthcare, 2015)
Objective. This study aimed to investigate the surface roughness of composite resins subjected to thermal cycles procedure. Materials and methods. Two microfill, four microhybrid and four nanofill composites were used. The surface roughness (Ra) was initially measured in a profilometer using a cut-off 0f 0.25 mm, after 3000 and 10,000 thermal cycles. Data were subjected to ANOVA and Fischer's test (alpha = 0.05). Results. Overall, 3000 thermal cycles increased the surface roughness values for all materials and there was a trend in all groups to decrease the roughness after 10,000 thermal cycles. Conclusions. The composition of material, including the type of organic matrix, could be more relevant to roughness maintenance over time than the general behavior of composites based on particles fillers. The maintenance of smooth surface in resin-based composite restorations is totally dependent of organic composition of the material.
Keywords: Roughness; Composite resin; Degradation